# (2-3x)(x+7)=0

## Simple and best practice solution for (2-3x)(x+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (2-3x)(x+7)=0 equation:

(2-3x)(x+7)=0
We add all the numbers together, and all the variables
(-3x+2)(x+7)=0
We multiply parentheses ..
(-3x^2-21x+2x+14)=0
We get rid of parentheses
-3x^2-21x+2x+14=0
We add all the numbers together, and all the variables
-3x^2-19x+14=0
a = -3; b = -19; c = +14;Δ = b2-4acΔ = -192-4·(-3)·14Δ = 529The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{529}=23$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-19)-23}{2*-3}=\frac{-4}{-6} =2/3$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-19)+23}{2*-3}=\frac{42}{-6} =-7$

`